The Effectiveness of the Implementation of the Electronic Health Center Management Information System (SIMPUStronik) on the Performance of Health Workers at the West City Health Center - Mutiara Juniarshi A. Mohune; Herlina Jusuf; Nikmatisni Arsad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The application of information technology as a health service is carried out at the Community Health Center (Puskesmas) so that along with the development of health service management needs, the government issued an Electronic Health Center Management Information System (SIMPUStronik) to mobilize work. The implementation of the Electronic Health Center Management Information System (SIMPUStronik) is the main need in the era of digitization of health services in Indonesia, especially in the West City Health Center as the health center with the highest accreditation in Gorontalo City. The implementation of SIMPUStronik at the West City Health Center has been going on since 2017, but it still faces various obstacles such as limited technology infrastructure, lack of training for health workers, and additional workload due to systems that have not been optimally integrated with existing workflows. The study used a quantitative approach with a total sampling technique, involving 55 health workers. Effectiveness is measured based on four main indicators, namely, target achievement, adaptability, user satisfaction, and responsibility. The results show that SIMPUStronik has high effectiveness in these four aspects, with the achievement of targets of 91%, adaptability of 91%, user satisfaction of 83%, and responsibility of 85%. The implementation of SIMPUStronik at the West City Health Center is very effective and has a positive impact on improving the performance of health workers. It is recommended for the West City Health Center to continue to be consistent in improving performance and monitoring the shortcomings of SIMPUStronics.